Impacts of Habitat Fragmentation on Terrestrial Biodiversity in Tropical Forests in Democratic Republic of Congo - Jenny, Rita (International Journal of Environmental Sciences, 2024)
Purpose: The aim of the study was to examine impacts of habitat fragmentation on terrestrial biodiversity in tropical forests in Democratic Republic of Congo Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that habitat fragmentation poses a significant threat to terrestrial biodiversity in tropical forests, particularly in the Democratic Republic of Congo (DRC). The fragmentation of forest habitats due to human activities such as logging, agriculture, and infrastructure development leads to the isolation of species populations, loss of genetic diversity, and disruption of ecological processes. As a result, endemic species in the DRC, including primates, birds, and large mammals, face heightened risks of population decline and extinction. Moreover, habitat fragmentation exacerbates other environmental challenges, such as climate change and invasive species encroachment, further compromising biodiversity conservation efforts in the region. Unique Contribution to Theory, Practice and Policy: Metapopulation Theory, Landscape Ecology Theory & Island Biogeography Theory may be used to anchor future studies on impacts of habitat fragmentation on terrestrial biodiversity in tropical forests in Democratic Republic of Congo. Implement habitat corridors that physically link fragmented habitats, facilitating the movement of species and genetic exchange. These corridors should be strategically placed based on ecological modeling to maximize effectiveness. Develop and enforce integrated land-use policies that consider both conservation and development needs. Policies should promote land-use planning that minimizes habitat fragmentation and incorporates ecological networks.